Sensitivity to Stroke Emerges in Kindergartners Reading Chinese Script - Li, Su; Yin, Li (Frontiers in Psychology, 2017)
To what extent are young children sensitive to individual stroke, the smallest unit of writing in Chinese that carries no phonological or semantic information? The present study examined Chinese kindergartners’ sensitivity to stroke and the contribution of reading ability and age to stroke sensitivity. Fifty five children from Beijing, including 28 4-year-olds (Mage=4.55 years, SD=0.28, 16 males) and 29 5-year-olds (Mage=5.58 years, SD=0.30, 14 males), were administered an orthographic matching task and assessed on nonverbal IQ and Chinese word reading. In the orthographic matching task, children were asked to decide whether two items were exactly the same or different in three conditions, with stimuli being correctly-written characters (e.g. “ ”), stroke-missing or redundant characters (e.g. “ ”), and Tibetan alphabets (e.g. “ ”), respectively. The stimuli were presented with E-prime 2.0 software and were displayed on a Surface Pro. Children responded by touching the screen and reaction time was used as a measure of processing efficiency. The 5-year-oldsbut not the 4-year-olds processed correctly-written characters more efficiently than stroke-missing/redundant characters, suggesting emergence of stroke sensitivity from age 5. The 4- and 5-year-olds both processed correctly-written characters more efficiently than Tibetan alphabets, ruling out the possibility that the 5 year olds’ sensitivity to stroke was due to the unusual look of the stimuli. Hierarchical regression analyses showed that Chinese word reading explained 10% additional variance in stroke sensitivity after having statistically controlled for age. Age did not account for additional variance in stroke sensitivity after having considered Chinese word reading. Taken together, findings of this study revealed that despite the visually highly-complex nature of Chinese and the fact that individual stroke carries no phonological or semantic information, children develop sensitivity to stroke from age 5 and such sensitivity is significantly associated with reading experience.